Pengaruh perbedaan gender pada hubungan pengalaman kerja audit dengan kualitas audit - Utama, Fikri Rizky; Anita, Lella (Jurnal Manajemen, 2024)
This research aims to obtain empirical evidence about the influence of audit work experience on audit quality. And its influence is moderated by gender differences. The population in this study are public accountants who work at KAP Bandar Lampung. The research method uses a survey method. And sampling used the convenience sampling method. The data collection technique is primary data using a questionnaire. And the data is processed using the Smart PLS program. The research results show that audit work experience has a significant effect on audit quality. And audit work experience also has a significant effect after being moderated by gender differences.